Effects of carbon addition on the microstructure, mechanical properties, corrosion resistance and tribological behaviour of Ti(C, N)-based cermets. (19th September 2018) - Zhang, Meimei; He, Yuehui; Lin, Nan; Kang, Xiyue
Abstract: In this work, the microstructure and properties of Ti(C, N)-based cermets with different carbon additions that were prepared by a powder metallurgy method were systematically studied through SEM, TEM, mechanical properties tests, electrochemical tests and friction tests. The results showed that the micromorphology of the core-shell structure in the cermets was strongly affected by carbon content. The increase in carbon addition can lead to a finer hard core phase and thicker rim phase in the cermets. In addition, both the fracture toughness and transverse rupture strength of cermets tended to increase first and then decrease with increasing carbon content, while hardness slowly decreased. The cermet with 0.3 wt% added carbon showed the highest fracture toughness (12.94 MPa · m 1/2 ) and transverse rupture strength (1961 MPa). Furthermore, the corrosion resistance of the cermets decreased with increasing carbon addition in 0.2 mol L −1 H2 SO4 solution during electrochemical tests on account of the alloying elements precipitating from the binder phase. Additionally, after room-temperature friction tests, the wear patterns of the cermets changed from abrasive wear to adhesive wear with increasing carbon addition due to the softening of the binder phase. However, plastic deformation and oxidation were the main wear behaviours of cermets in the high-temperature friction process.